Fourteenth century England. - Dodd, Gwilym (Fourteenth century England, 2018)
Drawing on a diverse range of documentary, literary and material evidence, the essays collected here consider a wide range of important issues for the period. Political and institutional history is addressed in essays on Edward II's personal expenditure and the development and workings of parliament, including an analysis of those neglected'parliamentarians'of the period, the parliamentary proctors. Important new insights into the social history of the fourteenth century are provided by chapters on marriage and the accumulation of lay estates, the brokerage of royal wardship and the important and difficult subject of sexual violence towards under-age girls. Another chapter considers the enormously costly and complex task of feeding and supplying medieval armies across the'long'fourteenth century, while two final pieces offer important new insights into the material culture of the age, focusing in turn on St Stephen's Chapel, Westminster, and the phenomenon of royal reburial. Richlytextured with personal and local detail, these new studies provide numerous insights into the lives of great and small in this fascinating period of medieval history. Gwilym Dodd is Associate Professor of Medieval History at the University of Nottingham. Contributors: Elizabeth Biggs, Anna M. Duch, Bridget Wells-Furby, Alan Kissane, Ilana Krug, Alison K. McHardy, Seymour Phillips, Laura Tompkins, Kathryn Warner.